Pengaruh Gaya Kepemimpinan Suportif, Kompensasi dan Kompetensi Terhadap Kinerja Karyawan PT. Wahana Pendawa Bakti - Sandra Gitani Tingkes; Diyan Lestari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The existence of the Covid-19 pandemic has a fairly large impact on the operations of a company, one of which is affected by PT. Wahana Pendawa Bakti. This study aims to determine the effect of Supportive Leadership Style, Compensation and Competence on employee performance at PT. Wahana Pendawa Bakti. The distribution of the questionnaire was 71 respondents using google form. This research uses a quantitative study with multiple regression analysis method and uses the SPSS25 program. The results of the study show that the Supportive Leadership Style, Compensation, and Competence partially influence the performance of the employees of PT. Bakti Pendawa Wahana. The findings of this study can be used as a reference for PT. Wahan Pendawa Bakti to evaluate the performance of its employees